A comparison of auditory and blind separation techniques for speech segregation. - Van der Kouwe, A.J.W.
A fundamental problem in auditory and speech processing is the segregation of speech from concurrent sounds. This problem has been a focus of study in computational auditory scene analysis (CASA), and it has also been investigated from the perspective of blind source separation. Using a standard corpus of voiced speech mixed with interfering sounds, we report a comparison between CASA and blind source separation techniques, which have been developed independently. Our comparison reveals that they perform well under very different conditions. A number of conclusions are drawn with respect to their relative strengths and weaknesses in speech segregation applications as well as in modeling auditory function
Keywords: Auditory function modelling; Auditory processing; Auditory separation; Blind separation; Blind source separation; Computational auditory scene analysis; Concurrent sounds; Interfering sounds; Speech processing; Speech segregation; Speech segregation applications; Voiced speech